Plant‐derived exosome‐like nanoparticles: A concise review on its extraction methods, content, bioactivities, and potential as functional food ingredient - Suharta, Sigit; Barlian, Anggraini; Hidajah, Atik Choirul; Notobroto, Hari Basuki; Ana, Ika Dewi; Indariani, Susi; Wungu, Triati Dewi Kencana; Wijaya, Christofora Hanny (Journal of food science, 2021)
Plant‐derived exosome‐like nanoparticles (PDENs) are small vesicles released by multivesicular bodies mainly to communicate between cells and regulate immunity against pathogen attack. Current studies have reported that PDENs could modulate gene expression in a cross‐kingdom fashion. Therefore, PDENs could be a potential future functional food ingredient as their cross‐kingdom communication abilities were reported to exert multiple health benefits. Macrophage and other cells have been reported to absorb PDENs in a manner regulated by the membrane lipid and protein profile and the intactness of the PDENs lipid bilayer. PDENs could be extracted from plant materials by various techniques such as ultracentrifugation, immunoaffinity, size‐based isolation, and precipitation, though each method has its pros and cons. PDENs mainly contain lipid, protein, and genetic materials, mainly micro RNAs, which could exert multiple health benefits and functionalities when consumed in sufficient amounts. However, most studies on the health functionalities of PDENs were conducted through in‐vitro and in‐vivo studies, and its potency to be used as a functional ingredient remains a question as PDENs are sensitive to storage and processing condition and requires costly extraction method. This concise review features various exosome extraction methods, contents of PDENs and their roles, the health functionalities of PDENs, and its potency as a functional food ingredient.